PRIMARY CARE: HOW TO INCREASE PHYSICAL ACTIVITY IN YOUR PATIENTS - A. L. Slobodyanyuk; I. A. Кrylova; V. I. Kupaev (SINAPS LLC, 2019)
Sedentary lifestyle, being a behavioral risk factor for chronic non-communicable diseases, is relevant for preventive medicine. A key role in the correction of behavioral risk factors for chronic non-communicable diseases is occupied by general medical practice, where the patient is continuously observed for many years. Increased physical activity reduces the risk of atherosclerosis, diseases of the musculoskeletal system, malignant tumors, has a positive effect on the psychological state of patients and reduces the overall morbidity and mortality. Increasing the reserves of the cardiorespiratory system of the body, physical activity improves the quality of life of patients and reduces the cost of medical care.To effectively combat sedentary lifestyle, it is necessary to adequately motivate patients that can be achieved through routine counseling to enhance physical activity. The method of such consultation should take into account limited time of outpatient admission and all personal characteristics of patients (starting level of physical activity, health group and risk of disease).The article presents a summary of modern scientific views in the field of increasing physical activity of patients, discusses current issues of counseling. The groups of patients with or without chronic diseases and the high risk of cardiovascular complications were discussed. The variant of rational outpatient counseling with the help of the algorithm of organization of physical activity mode, providing stratification of patients, planning, optimization and control of personal motor activity was presented. The proposed method of optimization of counseling successfully solves the problems of motivation, increase of physical activity and individual approach in outpatient practice.